Safety and Efficacy Analysis of Selinexor-Based Treatment in Multiple Myeloma, a Meta-Analysis Based on Prospective Clinical Trials - Tao, Yali; Zhou, Hui; Niu, Ting (Frontiers in Pharmacology, 2021)
Background: Selinexor is a novel agent that inhibits XPO1. The combination of selinexor (SEL) and dexamethasone (DEX) has been approved in the USA for patients with penta-refractory multiple myeloma. Clinical studies showed that SEL also had synergistic antimyeloma activity with other drugs. This meta-analysis aimed to investigate the safety and efficacy of selinexor based treatment in Multiple myeloma. Methods: We systematically searched the Medline, Embase, Web of Science, CENTRAL, and ClinicalTrials.gov. Outcome measures of efficacy included overall response rate (ORR), clinical benefit rate (CBR), stringent complete response rate (sCR), complete response rate (CR), very good partial response (VGPR), partial response rate (PR), minimal response (MR), rate of stable disease (SDR), rate of progressive disease (PDR) and median progression-free survival (mPFS). Safety was evaluated by the incidences of all grade adverse events and grade≥3 adverse events. The subgroup analysis was conducted to analyze the difference in different combination treatment regimens (SEL+DEX+PIs vs SEL+DEX). Results: We included 6 studies with 477 patients. The pooled ORR, CBR, sCR, CR, VGPR, PR, MR, SDR, and PDR were 43% (18%-67%), 55% (32%-78%), 5% (-2%-13%), 7% (4%-11%), 14% (5%-24%), 23% (15%-31%), 11% (8%-14%), 26% (14%-38%) and 14% (4%-23%), respectively. SEL+DEX+PIs treatment had higher ORR (54% vs 24%, P=0.01), CBR (66% vs 37%, P=0.01), sCR(10% vs 2%, P=0.0008), and VGPR (23% vs 5%, P<0.00001) compared to SEL+DEX treatment, and lower PDR (4% vs 23%, P<0.00001) and SDR (17% vs 37%, P=0.0006). The pooled incidences of any grade and grade≥3 were 45% and 30% in hematological AEs, and in non-hematological AEs were 40% and 30%, respectively. The most common all grade (68%) and grade≥3 (54%) hematological AE were both thrombocytopenia. Fatigue was the most common all grade (62%) and grade≥3 (16%) non-hematological AE. Compared to SEL+DEX treatment, SEL+DEX+PIs treatment had lower incidences of hyponatremia, nausea, vomiting, and weight loss in all grade AEs. Meanwhile, SEL+DEX+PIs treatment had lower incidences of anemia, fatigue, hyponatremia than SEL+DEX treatment in grade≥3 AEs. Conclusion: Selinexor-based regimens could offer reasonable efficacy and tolerable adverse events in patients with multiple myeloma. SEL+DEX+PIs treatments had higher efficacy and lower toxicities than SEL+DEX.